Study population density of the Green peach, Myzus persicae Sulz. in Nineveh - Abbasi, Shatha H. A.; Qasim, Nabil A.; Ali, Juhina Adrees (Journal of Kerbala for Agricultural Sciences, 2018)
This experiment was carried out in one of the fields of the Faculty of Agriculture and Forestry / University of Mosul and one of the private fields in the site of the dome during the growing season 2006, it was demonstrated from the results obtained according to the randomly sampling program in the two study locations in. The College and Al-Qubba, the insect was firstly appeared in the two locations at the beginning of September 2006 and then gradually increased to reach an Autumn peak of 472 insect in the College area, then the predator Coccinella sepetumpunctata L. and Aphidius transcaspicus Tele. appeared in the middle of October. The number of pest was increased estimated at the spring peak in the middle of March, and then disappeared due to the increasing number of predators and parasitoids in July. The pest appeared again in the 3rd week of November with an average 644 insect at the autumn peak in Al-Qubba. The population of the pest increased again estimated at the spring peak with an average of 520 insect in the middle of March with their natural enemies, so that the population pest was decreased and gradually disappeared in the end of July.